Penilaian Akuntabilitas Keuangan Sektor Publik untuk Menilai Kinerja Keuangan Pemerintah Kota Bandar Lampung - Salsabilla, Rani Velia; Alam, Iskandar Ali (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Regional autonomy policies implemented by local governments have a significant impact on their financial management efficiency. It is important to create competitiveness based on principles appropriate to the potential and unique characteristics of each region. Assessing regional financial performance is critical, especially in the context of high-quality accountability principles, including thorough evaluation of regional financial performance measures. This study uses a quantitative descriptive method, focusing on analyzing regional financial ratios. The data used comes from secondary sources, specifically the Bandar Lampung City Budget Achievement Report from 2019 to 2021. The research results show that the regional financial performance of Bandar Lampung City, if evaluated based on the regional financial independence ratio, is ranked at advisory level. However, the original regional income (PAD) efficiency ratio shows inefficiency in managing this source of income. In addition, the regional financial efficiency ratio shows that the level of efficiency has not yet reached the optimal level. PAD, gross income, and operating expenditure growth rates trended negatively, while capital expenditure growth rates trended positively.